2014
DOI: 10.1037/a0037780
|View full text |Cite
|
Sign up to set email alerts
|

With or without you: Preliminary evidence that attachment avoidance predicts nondeployed spouses’ reactions to relationship challenges during deployment.

Abstract: Although much is written about the impact of deployment on nondeployed spouses (NDSs) and couple relationships, few empirical studies address this directly. Using attachment theory as a guiding framework, this study followed 32 NDSs across a military deployment. We examined the prospective association between NDSs' attachment avoidance and their response to relational challenges (assessed using both correlational and experimental designs) during a deployment. Two weeks before deployment, NDSs provided self-rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 29 publications
2
48
1
2
Order By: Relevance
“…In line with recent work suggesting that brief theory-driven social psychological interventions can profoundly influence relational and individual well-being in an iterative way (Finkel et al, 2013;Layous et al, 2013;Sin & Lyubomirsky, 2009), our study adapted a brief relational savoring task (Borelli et al, 2010(Borelli et al, , 2014 for administration over the internet among adult members of LDRs; as primary outcomes, we assessed emotional reactions and relationship satisfaction following a simulated relationship stressor. Consistent with the study predictions, we found that assignment to the relational savoring condition (as opposed to either of the two control conditions) resulted in greater self-reported positive and lower negative emotion.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In line with recent work suggesting that brief theory-driven social psychological interventions can profoundly influence relational and individual well-being in an iterative way (Finkel et al, 2013;Layous et al, 2013;Sin & Lyubomirsky, 2009), our study adapted a brief relational savoring task (Borelli et al, 2010(Borelli et al, , 2014 for administration over the internet among adult members of LDRs; as primary outcomes, we assessed emotional reactions and relationship satisfaction following a simulated relationship stressor. Consistent with the study predictions, we found that assignment to the relational savoring condition (as opposed to either of the two control conditions) resulted in greater self-reported positive and lower negative emotion.…”
Section: Discussionmentioning
confidence: 97%
“…They were instructed to select any kind of experience, no matter how minor or major, when they felt especially "cherished, protected, or accepted" by their partner (Borelli et al, 2010(Borelli et al, , 2014, which was designed to evoke feelings of attachment security. Just as in the personal savoring condition, participants reported on the details of the event, as well as their thoughts and feelings, and then My alarm goes off.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although existing research demonstrates that personal relationships are the most commonly reported focus of savoring (Bryant et al, ), few studies have explicitly examined the differences between savoring an individual, personal memory ( personal savoring ) and savoring the memory of an experience that was shared with another person ( relational savoring ). Relational savoring involves deeply focusing one's attention on a moment of shared positive connection with another person (Borelli, Sbarra, et al, ; Bryant, ). Based on the general savoring literature, we would expect any type of savoring (personal or relational) to improve parents' emotions.…”
Section: Savoringmentioning
confidence: 99%